2008
DOI: 10.1177/1367493508096201
|View full text |Cite
|
Sign up to set email alerts
|

Hospital—school liaison: perspectives of health and education professionals supporting children with renal transplants

Abstract: This article explores collaboration between health and education staff as a key aspect of educational provision for children with chronic medical conditions, drawing upon material from interviews with eight health professionals (paediatric nephrologists and specialist renal nurses) and 11 mainstream schoolteachers involved in the care and schooling of children with renal transplants. Notwithstanding the apparent existence of good practice, a complex interplay of attitudinal, institutional and wider political a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 15 publications
(21 reference statements)
0
14
0
2
Order By: Relevance
“…Inter-specialty collaboration seems to be a major factor to many advances made in medicine in the developed countries. [3] For a specialty relatively new in Nigeria, paediatric surgery needs profound amounts of collaboration with other specialties in order to achieve good outcomes. This survey has shown that collaboration is presently desirable but inadequate between paediatric surgery and other specialties in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Inter-specialty collaboration seems to be a major factor to many advances made in medicine in the developed countries. [3] For a specialty relatively new in Nigeria, paediatric surgery needs profound amounts of collaboration with other specialties in order to achieve good outcomes. This survey has shown that collaboration is presently desirable but inadequate between paediatric surgery and other specialties in Nigeria.…”
Section: Discussionmentioning
confidence: 99%
“…Although educational support on hospital haemodialysis is mandated in many countries, it was only available in 10 of the 14 European units surveyed [31]. In our own unit we endeavour to maintain a close liaison with school, whether the child is on haemodialysis, CPD or post-transplant [51]. One of the teachers attends clinic to liaise with families and extra educational support has been provided during summer holidays.…”
Section: Educationmentioning
confidence: 99%
“…There is evidence that there are factors that make any collaboration between educational and health care systems difficult (Poursanidou, Garner, & Watson, 2008). There is a lack of understanding on the part of both health care providers and educators regarding the other’s roles and responsibilities regarding CSHCN.…”
Section: Discussionmentioning
confidence: 99%